Can metalinguistic awareness explain a connection between L1 literacy and L2 proficiency level in literate adults? - Xhafaj, Donesca (2011)
Recently, Bigelow, Delmas, Hansen, and Tarone (2006) arguedthat the differences in the oral performance of their L2 speakers(favoring the more literate ones) were probably due to their lowlevel of metalinguistic awareness (which would be a consequenceof their limited literacy). So as to contribute with evidence for thishypothesis, we collected data from 11 Brazilians, who performedtests of L1 literacy, L2 proficiency and L1 and L2 metalinguisticawareness (phonological, morphological, and syntactic) and arelationship between their L1 literacy and their L2 proficiencylevels was, indeed, found. However, the role metalinguisticawareness (either in the L1 or the L2) plays in this relationshipis not clear. While phonological awareness (in the L1 and in the L2) was related to L1 literacy and L2 proficiency, morphologicalawareness (in the L1, only) and syntactic awareness (in theL2, only) were only related to L2 proficiency. Though theseinconclusive results might be the artifact of limitations in someof the instruments used to collect data, this seems to be a fruitfulline of research.